PENGARUH EVALUASI PENGENDALIAN INTERNAL DAN PENERAPAN DUE PROFESSIONAL CARE TERHADAP KUALITAS AUDIT - Budi Tri Rahardjo, Ak., M.Ak., CA; Jeane Widia Ningsi (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2019)
This research conducted with the aim of testing the extent of the evaluation of internal control and the application of due professional care to audit quality in KAP Ispiady & Dande. This research uses quantitative analysis. In this study, researchers used primary data by distributing questionnaires to KAP Ispiady & Dande employees. Then the data analyzed using multiple linear regression analysis with the help of the statistical package for Social Sciences (SPSS) version 22. The results showed that the internal control variable and the due professional care variable had a significant influence on audit quality and the results showed that the two independent variables jointly have a significant influence on audit quality